1900
DOI: 10.1039/ct9007700069
|View full text |Cite
|
Sign up to set email alerts
|

VII.—The oxidation of organic acids in presence of ferrous iron. Part I

Abstract: THE oxidation of various organic substances by means of hydrogen dioxide and other agents in presence of small quantities of iron salts, has formed the subject of a considerable number of communications to the Society and elsewhere (compare Fenton,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 0 publications
0
23
0
3
Order By: Relevance
“…Under these conditions lipid peroxyl or alkoxyls formed may have resulted in oxidation of unsaturated lipids, as predicted by Halliwell and Gutteridge [15,16]. Following Fenton's demonstration [10] that ferrous salts can act ''catalytically'' with H 2 O 2 to yield hydroxyl radicals [20], we have observed that at millimolar levels, FeCl 2 has a dose-response relationship with the biophysical properties of surfactant. Iron is the most abundant transition metal in the body, and because of wide variations in its redox potential it can behave as a prooxidant to participate in free radical production.…”
Section: Discussionmentioning
confidence: 82%
“…Under these conditions lipid peroxyl or alkoxyls formed may have resulted in oxidation of unsaturated lipids, as predicted by Halliwell and Gutteridge [15,16]. Following Fenton's demonstration [10] that ferrous salts can act ''catalytically'' with H 2 O 2 to yield hydroxyl radicals [20], we have observed that at millimolar levels, FeCl 2 has a dose-response relationship with the biophysical properties of surfactant. Iron is the most abundant transition metal in the body, and because of wide variations in its redox potential it can behave as a prooxidant to participate in free radical production.…”
Section: Discussionmentioning
confidence: 82%
“…Hence we examined the possibility of reversing oxyradical-induced physiological damage to lenses in culture by using pyruvate. Pyruvate was selected because in addition to its action as an oxyradical scavenger [12][13][14] , it has been found to act as a metabolic agonist and even inhibit glycation of tissue proteins associated with cataract formation [15,16] . The results were in accordance with this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies investigating the association of antioxidant vitamins and a lowered incidence of cataracts have yielded results that are yet equivocal [13][14][15]. Hence we considered the desirability of studying the anti-cataractogenic potential of certain endogenously derived ROS scavengers such as pyruvate, a keto acid metabolite well-known to scavenge various ROS, with rate constants of reaction reaching the diffusion limit [16,17]. This is especially true with respect to hydroxyl radical [18].…”
Section: Research Articlementioning
confidence: 99%